Formulating Islamic jurisprudence framework for stratified properties management - Mohamad, Nor Asiah (IDOSI Publications, 2017)
This paper prepares a basis for formulating a coherent and systematic jurisprudence of stratified properties management from an Islamic perspective. It promotes that stratified building management which allows for self management among the property owners forms a basis for positive relationship thus promoting the concept of Hablum Minallah (relationship with Allah) and Hablum Minannas (relationship among the fellow human being), sustainability, ecological awareness as well as accountability to the Creator (Allah). This paper employs a doctrinal analysis where the verses from the Quran and the compilation of the authentic hadith are used as a basis for developing a framework towards producing comprehensive jurisprudential guidelines for stratified properties management. The findings show that there is dearth of guideline from the primary sources on property management. Nevertheless, Islam laid down various general principles to form a guideline on how a Muslim manages his matters privately and with the public. The details are left to be determined via various methods of jurisprudential and legal analysis. This paper proposes that human being’s roles in stratified properties management should be regulated based on Islamic jurisprudence perspective where understanding of the objectives [maqasid] of the Shari'ah is of primary concern. Key words: Stratified properties management Strata titles Land Islamic jurisprudence Maqasid Shariah